The Phosphate Inhibition Paradigm: Host and Fungal Genotypes Determine Arbuscular Mycorrhizal Fungal Colonization and Responsiveness to Inoculation in Cassava With Increasing Phosphorus Supply - Peña Venegas, Ricardo Alexander; Lee, Soon-Jae; Thuita, Moses; Mlay, Deusdedit Peter; Masso, Cargele; Vanlauwe, Bernard; Rodriguez, Alia; Sanders, Ian R. (Frontiers in Plant Science, 2021)
A vast majority of terrestrial plants are dependent on arbuscular mycorrhizal fungi (AMF) for their nutrient acquisition. AMF act as an extension of the root system helping phosphate uptake. In agriculture, harnessing the symbiosis can potentially increase plant growth. Application of the AMF Rhizophagus irregularis has been demonstrated to increase the yields of various crops. However, there is a paradigm that AMF colonization of roots, as well as the plant benefits afforded by inoculation with AMF, decreases with increasing phosphorus (P) supply in the soil. The paradigm suggests that when fertilized with sufficient P, inoculation of crops would not be beneficial. However, the majority of experiments demonstrating the paradigm were conducted in sterile conditions without a background AMF or soil microbial community. Interestingly, intraspecific variation in R. irregularis can greatly alter the yield of cassava even at a full application of the recommended P dose. Cassava is a globally important crop, feeding 800 million people worldwide, and a crop that is highly dependent on AMF for P uptake. In this study, field trials were conducted at three locations in Kenya and Tanzania using different AMF and cassava varieties under different P fertilization levels to test if the paradigm occurs in tropical field conditions. We found that AMF colonization and inoculation responsiveness of cassava does not always decrease with an increased P supply as expected by the paradigm. The obtained results demonstrate that maximizing the inoculation responsiveness of cassava is not necessarily only in conditions of low P availability, but that this is dependent on cassava and fungal genotypes. Thus, the modeling of plant symbiosis with AMF under different P levels in nature should be considered with caution.